NILAI-NILAI KEPENDIDIKAN DALAM AL SALA - Ma'arif, M. Jauharul (Universitas Nahdlatul Ulama Sunan Giri, 2019)
“Sala>t Al Nawa>fil (Tahajjud Prayers and Duha> Prayers) are one of the services which are also educational and training facilities to be sincere, have high enthusiasm, productivity, optimism, perseverance, and are motivated to become righteous servants. Duhuha Prayers and Tahajjud Prayers will bring up these values ​​if they are carried out in accordance with the prescribed rules and the motivation to take lessons from the worship performed.”",